Measurement of Childhood Serious Emotional Disturbance: State of the Science and Issues for Consideration. (December 2017) - Ringeisen, Heather; Stambaugh, Leyla; Bose, Jonaki; Casanueva, Cecilia; Hedden, Sarra; Avenevoli, Shelli; Blau, Gary; Canino, Glorisa; Carter, Alice; Colpe, Lisa; Copeland, William E.; Fisher, Prudence W.; et al.
Surveys suggest that between 4.3% and 11.5% of children living in the United States have a serious emotional disturbance (SED). SED is defined in the Federal Register, and federal block grants are allocated to states based on the prevalence of SED. Accurate measurement of SED is critical, yet surveys have used different methodologies and instrumentation to obtain prevalence estimates. Two expert panels were convened by the Substance Abuse and Mental Health Services Administration (SAMHSA) in the fall of 2014 to discuss the current state of the field in operationalizing and measuring SED. The aims of this article are to (a) provide an update on SED prevalence rates from survey research, (b) summarize key discussion points that emerged during the SAMHSA expert panel meetings, and (c) make specific recommendations for next steps in measuring the prevalence of SED. Issues addressed in this article are important not only for federal allocation of service dollars to meet the needs of children with SED, but also for broader mental health surveillance efforts within the context of large national research surveys.